1999
DOI: 10.1021/la9815143
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Monolayers of Small Aromatic Disulfide and Diselenide Molecules on Polycrystalline Gold Films:  A Comparative Study of the Geometrical Constraint Using Temperature-Dependent Surface-Enhanced Raman Spectroscopy, X-ray Photoelectron Spectroscopy, and Electrochemistry

Abstract: A detailed investigation of the self-assembled monolayers of diphenyl disulfide (DDS), diphenyl diselenide (DDSe), and naphthalene disulfide (NDS) on polycrystalline gold films using surface-enhanced Raman spectroscopy (SERS), X-ray photoelectron spectroscopy (XPS), and electrochemistry is presented. Whereas DDS dissociatively chemisorbs on Au, in both DDSe and NDS, the Se−Se and S−S bonds, respectively, are preserved upon adsorption. All of the molecules adsorb with the molecular plane perpendicular to the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(118 citation statements)
references
References 43 publications
5
112
1
Order By: Relevance
“…This could be due to the easy relaxation appearing from bond cleavage for DDSe and DDS, while for NDS, the fused ring may impose constraints for side movement and a lesser interaction affinity of DDSe than for the corresponding disulfides. These results underline the importance of intramolecular conformational changes in controlling the monolayer packing density and is in agreement with the results of surface-enhanced Raman spectroscopy (SERS) investigations (17).…”
Section: Quartz Crystal Microbalance (Qcm)supporting
confidence: 90%
See 1 more Smart Citation
“…This could be due to the easy relaxation appearing from bond cleavage for DDSe and DDS, while for NDS, the fused ring may impose constraints for side movement and a lesser interaction affinity of DDSe than for the corresponding disulfides. These results underline the importance of intramolecular conformational changes in controlling the monolayer packing density and is in agreement with the results of surface-enhanced Raman spectroscopy (SERS) investigations (17).…”
Section: Quartz Crystal Microbalance (Qcm)supporting
confidence: 90%
“…All other chemicals used in this work were purchased from Aldrich Co. and were used as received. Before the SAMs were deposited, the substrates were cleaned by the standard cleaning procedure described earlier (17). After repeated cleaning cycles using sulfochromic acid, aqueous HF, and deionized water, the substrates were blown dry with pure argon and were immediately transferred into a deaerated 1 mM solution of the appropriate compound in acetonitrile.…”
Section: Methodsmentioning
confidence: 99%
“…SAMs of dialkyl chalcogenides on Au(111) have been studied by Nakamura et al, and they found that selenides form ordered monolayers on Au(111) with long exposure time, whereas tellurides form disordered monolayers [34]. A detailed investigation of the selfassembled monolayers of diphenyl disulfide (DDS), diphenyl diselenide (DDSe), and naphthalene disulfide (NDS) on polycrystalline gold films was performed recently [35]. Whereas DDS dissociatively chemisorbs on Au, in both DDSe and NDS, the Se-Se and S-S bonds, respectively, are preserved upon adsorption.…”
Section: Adsorption and Structure Of Samsmentioning
confidence: 99%
“…Numerous methods can be used to obtain rough metals substrates, including plasma treatment [11], sputtering coating [3,15], mechanically polishing by using abrasives [16] and vacuum evaporation deposition [4,9,12,17,18]. However, a controllable and reproduced surface roughness can be generated through control of the electrochemical oxidation-reduction cycles (ORC) procedure [19].…”
Section: Introductionmentioning
confidence: 99%
“…In chemical enhancement, most studies [1,3,5,11,22] were devoted to molecules adsorbed on activated metals surfaces, especially to pyridine adsorbed on roughened silver [14,18,23,24]. Plays et al [20] studied the oxidation behavior of poly-1,8-diaminonaphthalene thin film, preparing by a cyclic voltammetry method, deposited on electrochemically roughened metals via SERS spectrum.…”
Section: Introductionmentioning
confidence: 99%